Optimization of lipase immobilization on nylon -6-grafted with PGMA polymer - Bahrudin, Nik Adlin; Al-Khatib, Ma'an Fahmi Rashid; Nasef, Mohamed Mahmoud (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)

(untitled)
Lipase from wheat germ was immobilized by covalent binding on a nylon -6- grafted with PGMA. This polymer was successfully activated with diethyl amine to intact with lipase enzyme molecule. Response surface methodology (RSM) was applied to model and optimize immobilization conditions for maximum activity and understanding the interaction of the factors affecting the activity of the immobilized enzyme. The face centered central composite design (FCCCD) was applied to measure the effect of reaction pH (6-8), reaction time (2-10 h) and enzyme concentration (1-2 mg) on enzyme activity. The result showed that pH, time and enzyme concentration had significant effects on the activity of lipase enzyme. Based on the analysis, the optimum immobilization conditions obtained were at pH 7, immobilization time 5 hours and enzyme concentration 0.90 mg/ml.